1994
DOI: 10.1210/endo.134.3.8119142
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta stimulates endometrial stromal apoptosis in vitro.

Abstract: Active growth and differentiation of endometrial stromal cells during the decidualization of early pregnancy are followed by programmed cell death (apoptosis) in the antimesometrial region of the decidua. The location and temporal specificity of decidual cell apoptosis and the identification of transforming growth factor-beta 1 (TGF beta 1) and TGF beta 2 protein and mRNA in the decidua suggested that members of the TGF beta family control stromal apoptosis by autocrine or paracrine mechanisms. To examine this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 16 publications
4
58
0
1
Order By: Relevance
“…Recently, Ladin et al (1998) showed that clinically relevant doses of corticosteroids and interferon-␥ induce an increase in apoptosis of keloid-derived fibroblasts. Recent investigators believe that one of the triggers of apoptosis is growth factor withdrawal during differentiation (Laster et al, 1988;Moulton, 1994;Oberhammer et al, 1993;Robaye et al, 1991). This is consistent with the present results that serum deprivation significantly increases caspase-3 proteolytic activity and apoptosis in KFB lines.…”
Section: Akasaka Et Almentioning
confidence: 99%
“…Recently, Ladin et al (1998) showed that clinically relevant doses of corticosteroids and interferon-␥ induce an increase in apoptosis of keloid-derived fibroblasts. Recent investigators believe that one of the triggers of apoptosis is growth factor withdrawal during differentiation (Laster et al, 1988;Moulton, 1994;Oberhammer et al, 1993;Robaye et al, 1991). This is consistent with the present results that serum deprivation significantly increases caspase-3 proteolytic activity and apoptosis in KFB lines.…”
Section: Akasaka Et Almentioning
confidence: 99%
“…145 The lethal effect of TGF-b2 has been demonstrated in primary cultures of rat decidualized stromal cells which showed an increase in the incidence of cell death (internucleosomal DNA fragmentation) when exposed to the growth factor. 146 Other experiments suggest that uterine epithelial cells may be another target for the pro-apoptotic activity of TGF-b1. Administration of TGF-b1 into the uterine stroma of estradiol-sustained ovariectomized mice resulted in an increased incidence of cell death in the adjacent epithelial layer (condensation of chromatin and cytoplasm materials, positive TUNEL staining) 147 and addition of TGF-b1 to primary cultures of mouse epithelial cells triggered a similar effect.…”
Section: Mechanisms Of Cell Death In the Uterusmentioning
confidence: 99%
“…In addition, statistically significant negative correlations were found between the level of DNA fragmentation and sperm motility (r=-0.646; p=0.001), and abnormal sperm morphology (r=0.434; p=0.001). However no evident correlation was found between the percentage of sperm DNA fragmentation and sperm count, and paternal age (p>0.05) [39].…”
Section: Analysis Of Sperm Dna Fragmentationmentioning
confidence: 84%
“…The eosinnigrosin viability test was performed by dissolving 20μl eosin with 20μl of fresh sperm and then 20μl nigrosin [37][38][39].…”
Section: Determination Of Necrospermiamentioning
confidence: 99%